Association between the triglyceride glucose index and cognitive impairment and dementia: a meta-analysis - Wang, Huan; Ling, Qin; Wu, Yifan; Zhang, Mingjie (Frontiers in Aging Neuroscience, 2023)
Background The triglyceride and glucose (TyG) index is an alternative index of insulin resistance (IR). We aimed to clarify the relationship between the TyG index and cognitive impairment and dementia. Methods We conducted a comprehensive search of the PubMed, Cochrane Library, and Embase databases until February 2023 to identify relevant studies. Random-effects models were used to pool effect sizes, and the Grading of Recommendations Assessment, Development, and Evaluation system (GRADE) was used to assess the quality of the evidence. Results Ten studies were included, with seven of which investigated the relationship between the TyG index and cognitive impairment and three exploring the association between the TyG index and dementia. When the TyG index was described as a categorical variable, it was positively associated with the risk of cognitive impairment (OR = 2.32; 95% CI 1.39–3.87) and dementia (OR = 1.14, 95% CI 1.12–1.16). The association of the TyG index with the risk of cognitive impairment (OR = 3.39, 95% CI 1.67–6.84) and dementia (OR = 1.37, 95% CI 1.03–1.83) remained significant for per 1 unit increment in the TyG index. The GRADE assessment indicated a very low certainty for cognitive impairment. Low certainty and moderate certainty were observed for dementia when the TyG index was analyzed as a categorical variable and as a continuous variable, respectively. Conclusion The TyG index is associated with an increased risk of cognitive impairment and dementia. Further prospective research is warranted to confirm these findings. Systematic review registration: https://www.crd.york.ac.uk/, Protocol registration number: CRD42023388028.